Kiran Nagarkar’s metro-life novels - JITENDRA KUMAR (International Journal of Multidisciplinary Research and Studies, 2021)
A social and cultural study is a part of every piece of written literature. According to the dictionary, the phrase "pertaining to society or its organization" best describes the meaning of this term. The author shines light on a variety of organizations as well as aspects of social life. In his work, he addresses a number of different societal concerns that he has chosen. Ziauddin Sardar and Borin Van Loon make the following assertion in their book: "The field of study known as "cultural studies" is one that is both fascinating and current. It has gained traction among progressives of all kinds, not the least of which is due to the fact that culture has displaced society as the major subject of their investigation. It is currently considered a fundamental component of academic writing in many disciplines, including the humanities, social sciences, natural sciences, and even technical professions. When we live in a certain culture, we only learn a limited amount about that society’s history and traditions. The study of culture is like to looking at an iceberg. We are unable to fathom the cultural aspirations and ideals that lie under the surface. One of the oldest definitions of culture was developed by the British anthropologist Sir E. B. Tylor (1832–1972) His description was as follows: "There is a lot of room for interpretation when it comes to the idea of culture; some anthropologists consider culture to be social behavior. Some people regard it more as an abstraction derived from behavior than as the real behavior itself.